1999
DOI: 10.4141/a97-091
|View full text |Cite
|
Sign up to set email alerts
|

Plane of nutrition and folic acid supplementation between birth and four months of age on mammary development of dairy heifers

Abstract: . 1999. Plane of nutrition and folic acid supplementation between birth and 4 months of age on mammary development of dairy heifers. Can. J. Anim. Sci. 79: 227-234. Forty-seven dairy heifers of approximately 10 d of age were assigned randomly to a 2 × 2 factorial design to study the effects of folic acid supplementation (0 vs. 40 mg) administered weekly i.m. and levels of feed intake after weaning on mammary development. Folic acid treatment started immediately and all heifers were weaned 5 wk later. Heifers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 37 publications
2
13
1
6
Order By: Relevance
“…Results from this current study are similar to those reported previously in that the high diet increased fat deposition in extraparenchymal fat and this was also found to be evident in perirenal fat. Parenchymal tissue adjusted for carcass weight also followed a similar trend to that reported in the literature (Sejrsen et al, 1982;Petitclerc et al, 1999). However, analysis of mammary tissue composition is ongoing and must be completed before fi nal conclusions are made.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Results from this current study are similar to those reported previously in that the high diet increased fat deposition in extraparenchymal fat and this was also found to be evident in perirenal fat. Parenchymal tissue adjusted for carcass weight also followed a similar trend to that reported in the literature (Sejrsen et al, 1982;Petitclerc et al, 1999). However, analysis of mammary tissue composition is ongoing and must be completed before fi nal conclusions are made.…”
Section: Discussionsupporting
confidence: 71%
“…But, mammary development and milk yield potential are hindered when prepubertal dairy heifers are fed for a high rate of gain for lengths of time greater than 3 months (Sejrsen et al, 1982;Petitclerc et al, 1999;Radcliff et al, 2000). However, the effects of a high rate of gain for shorter periods have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lee et al, () found that plasma IGF‐1 increased with increasing dietary CP level in steers. However, Petitclerc et al, () found that serum GH and IGF‐1 were unaltered with 40 mg FA intramuscular injection weekly in dairy heifers. The higher FA supplementation dose (about 176 mg weekly) of the current study should be the reason for the divergent results.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary FA supplementation could promote milk protein synthesis by elevating the transfer efficiency of one‐carbon units (Girard, Lapierre, Matte, & Lobley, ; Graulet et al, ). Average daily gain (ADG) was increased with intramuscular injection of FA in calves (Dumoulin, Girard, Matte, & StLaurent, ; Petitclerc, Dumoulin, Ringuet, Matte, & Girard, ). Yields of milk and milk protein were increased with FA supplementation in dairy cows (Graulet et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, literatures have demonstrated that folic acid administered by intramuscular injections or dietary supplementation improved the growth of weaned dairy calves (Petitclerc et al, 1999) and heifers (Dumoulin et al, 1991) and increased milk yields and milk component production in dairy cows (Girard and Matte, 1998;Graulet et al, 2007;Li et al, 2016). Furthermore, some literatures reported that the synthesis of folic acid in the rumen ranged from 16.5 to 21.0 mg/d in dairy cows (Santschi et al, 2005;Schwab et al, 2006), while the estimated folic acid requirement of a cow with 650 kg BW and 35 kg of fat-corrected milk yield was 35 mg/d (NRC, 2001).…”
Section: Introductionmentioning
confidence: 99%